Extent of compliance to the DECS 1988 minimum library standards and PAASCU library standards of selected private secondary school libraries in Quezon City - Lisondra, Fiona Z. (2001)
Education, as one important aspect of man's quest for knowledge, is never complete without the sources of information, whether print or non-print. These sources of information are housed in a special place within a learning institution called "library". The library is one major contributor in the teaching-learning process of school in bringing about literacy to people.